Description of Achromadora gracilis n. sp. and observations on A. micoletzkyi (Stefanski, 1915) Van der Linde, 1938 y Ethmolaimus multipapillatus Paramonov, 1926 (Nematoda: Chromadorida) from Spanish lakes - Ocaña A, .Hernández J. A., Monterrubio, E (Zoológica baetica, 1999)
Three species of Chromadorida have been found for the first time in continental waters in Spain. Two of these belonging to the genus Achromadora Cobb, 1913, were found in high-mountain lakes in Sierra Nevada Mountains (Granada) at an altitude of over 2700 m.a.s.l.: Achromadora micoletzkyi (Stefanski, 1915) Van der Linde, 1938 and A. gracilis n. sp. The third species, Ethmolaimus multipapillatus Paramonov, 1926 was found in the hypersaline lake Fuente Piedra in Archidona (Málaga Province). A description of A. gracilis n. sp. is given. In addition, environmental date of two congeneric species (A. gracilis and A. micoletzkyi) are discussed. Supplementary morphological-anatomical and environmental data are provided for E. multipapillatus.